A Aliança Tabebuia (Bignoniaceae) no Estado da Bahia, Brasil - Espírito Santo, Fábio da Silva do (2012)
Bignoniaceae is the most important family of lianas in the Neotropics, and has a center of diversity in Brazil. In spite of the high representativeness of species in the country and the high ecological and economic importance of the family, the group has been scarcely investigated from the viewpoints of taxonomy and floristics. The objective of this study was to prepare a taxonomic treatment of the Tabebuia Alliance (Bignoniaceae) in the state of Bahia. This Alliance represents a clade composed of tribe Crescentieae and several species previously belonging to tribe Tecomeae. The monograph is divided in four chapters: in Chapters I and II, three new species of Handroanthus are described (H. diamantinensis, H. grandiflorus, and H. parviflorus); in the Chapter III, the taxonomic treatment of Tabebuia Alliance from the state of Bahia is presented; and in Chapter IV, an interactive identification key for the group is introduced, which makes the process more dynamic and playful. The Flora is based on field collection trips and collections in the herbaria ALCB, BAH, BHCB, CEN, CEPEC, HRB, HST, HUEFS, HUESB, HUESC, IBGE, IPA, MBM, R, RB, SP, SPF, UB e UFP. A total of six genera and 26 species were identified for Bahia: Cybistax (C. antisyphilitica), Godmania (G. dardanoi), Handroanthus (14 species), Sparattosperma (2), Tabebuia (6), and Zeyheria (2). Besides the new species, three new occurrences (H. cf. botelhensis, H. pedicellatus and T. reticulata) were also recorded for the state and for the Northeastern Brazil, with five species being endemic to the state of Bahia. Identification keys, descriptions, illustrations, distribution maps and general comments are provided for all species.